PENERAPAN SISTEM PENGENDALIAN INTERN TERHADAP PEMBERIAN KREDIT PADA PT PEGADAIAN (PERSERO) UNIT PELAYANAN CABANG KALIWUNGU - Arini Amalia Rahma; Siti Mutmainah (Politeknik Negeri Semarang, 2020)
Internal control is a process carried out by the company to provide adequate guarantees for achieving control objectives. The objective of this Research is to find out the current internal control system that is applied at PT Pegadaian (Persero) Kaliwungu Branch Service in the process of granting credit. The next objective is to identify whether the components of internal control applied are according to COSO. The data used are qualitative data, primary data, and secondary data. The methods of collecting data are interview, observation, and questionnaire. For writing the Research uses descriptive and exposition methods. There are five components of internal control according to the Committee of Sponsoring Organization (COSO), they are Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring. The results of the discussion in the Research shows that the application of the internal control system for granting credit at PT Pegadaian (Persero) Kaliwungu Branch Service is in accordance with COSO internal control component, but the Control Environment and Control Activities has not been fully implemented.